Determinants of effective Tax Rate of the top 45 Largest listed companies of Indonesia - Andreas, Dr.; Savitri, Enni (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
The capital inflows and outflows of a country are closely related to the established tax rate policy. Tax rate is one of important factors in investment decisions. Evidence that there are variations in effective tax rates amongs firms draw attention of researchers to understand the impact of tax policies on corporate tax burdens (Gupta and Newberry, 1997; Molloy, 1998). Effective tax rate is a dependent variable that is commonly used as a proxy to measure corporate tax burden. This study examined corporate effective tax rates (ETRs) of the top 45 largest listed companies of Indonesia within 2009-2014 (after tax reform of 2008, to be exact). We used two types of ETR1 and ETR2 measures as dependent variables. The first type is the ratio of current income tax expense divided by income before interest and taxes and the second type is the ratio of total income tax expense (current tax expense plus deferred tax expense) divided by income before interest and taxes (Noor et al. 2008).We also used some of independent variables related to firms’characteristics, such as firm size, capital intensity, leverage, returns on assets, and inventory intensity. The statistical results reveal that all independent variables contributed to ETR1 and ETR2 except the capital intensity is not contributed to ETR2. However, the findings provide support for the tax policy on corporate actual tax burdens.